Nutrient dynamics in paddy soil under rice culture mesocosm studies - Islam, MA; Khan, MA; Rouf, MA (Journal of the Bangladesh Agricultural University, 2017)
The objectives of this study were to determine the nutrient losses through the soil columns with the variation of soil and fertilizer. The experiment was conducted in a net house of Sher-e-BanglaAgriculturalUniversity, Dhaka, Bangladesh during July–November to study the effect of fertilizer and manure on the growth and yield of T. aman rice and leaching loss of nutrients through undisturbed soil columns. The experiment consists of 2 factors i.e. soils and fertilizer plus manure. Two soils (S1= SAU Soil and S2= Sonargaon Soil) with 4 levels of fertilization, as F0: Control, F1: 100% N120P20K45S20 (FRG 2012), F2: 50% NPKS + 5 t/ha cowdung, F3: 50% NPKS + 2.1 t/ha poultry manure were used in the experiment. T. Aman (BR11) rice was grown in the soil cores. Altogether, there were 8 treatment combinations and the treatment combinations were replicated 3 times. Twenty four undisturbed soil cores collected in PVC pipes were placed at the bottom of the perforated plastic containers and two holes of each plastic container were connected to a conical flask that was used to collect column leachate. Leachates were collected at 25, 35, 45, 55, 65 and 75 DAT (Days after transplanting) and analyzed for N, P, K and S. The leachate N, P, K and S concentration varied with different soil, fertilizer and time. The higher N and S concentrations were found in the leachate of SAU soil and higher leachate K concentrations were obtained in Sonargaon soil. The higher amounts of N leaching were observed during 45–55 DAT and higher leachate N concentrations were found in F1 treatment. Higher leachate K concentrations were found in 100% chemical fertilizer treatment and higher leachate K concentrations were found at 35DAT in all fertilizer treatments. The leachate P concentration increased at 35 DAT and then decreased. Results revealed that soil had no significant effect on the yield and yield parameters. The yield contributing characters and yields were significantly affected by fertilizer and manure application. The highest effective tillers/core (17.0), plant height (105.6 cm), panicle length (23.70 cm), grain yield (0.046 kg/core) and straw yield (0.053 kg/core) of T. Aman rice were found from F1 (RDCF) treatment. The highest 1000-grain wt. (23.70 g) was obtained from F2 and filled grain/panicle (121.8) from T3 treatment and the lowest in F0 treatment. The highest grain yield was found by the application of recommended dose of chemical fertilizer which was statistically similar to F3 (50% NPKS + 2.1 ton poultry manure) treatment. The combined effects of soil and fertilizer were not significant but the highest grain (0.049 kg/core) and straw yields (0.056 kg/core) were recorded from S2F1 (Sonargaon Soil + 100% NPKS) treatment combination. J. Bangladesh Agril. Univ. 15(2): 199-205, December 2017